Development of E-Module Physics Based on Local Wisdom of Lampung Written Batik on Temperature and Heat Materials - Yuberti; Yani Suryani; Sri Latifah; Sera Okta Pela (Impulse: Journal of Research and Innovation in Physics Education, 2022)
Students still think learning physics is boring. For this reason, educators are expected to be able to develop fun physics learning in various ways. This study aims to develop a module based on the local wisdom of Lampung written batik on temperature and heat. The research method used is research and development (R&D) with a Borg and Gall development model design. This research resulted in a product in the form of an e-module based on local wisdom of Lampung written batik on temperature and heat material with 90% media validation results, 91% material experts, and 82% IT experts. The percentages generated in the study indicate that the category is very feasible. Very feasible means that the developed module can be tested and applied to the next process. The trial was divided into two, namely a small trial of students who obtained 86% results in the very interesting category and field trials with teachers in three schools getting 89% results, and field trials of students getting 82% results. From the results of the small test percentage and field trials, the percentage is obtained in a very attractive category. The very interesting category means that the modules developed are well responded to and accepted by students and teachers. This research concludes that an e-module based on local wisdom of Lampung written batik has been developed on the material of temperature and heat. Students still think learning physics is boring. For this reason, educators are expected to be able to develop fun physics learning in various ways. This study aims to develop a module based on the local wisdom of Lampung written batik on temperature and heat. The research method used is research and development (R&D) with a Borg and Gall development model design. This research resulted in a product in the form of an e-module based on local wisdom of Lampung written batik on temperature and heat material with 90% media validation results, 91% material experts, and 82% IT experts. The percentages generated in the study indicate that the category is very feasible. Very feasible means that the developed module can be tested and applied to the next process. The trial was divided into two, namely a small trial of students who obtained 86% results in the very interesting category and field trials with teachers in three schools getting 89% results, and field trials of students getting 82% results. From the results of the small test percentage and field trials, the percentage is obtained in a very attractive category. The very interesting category means that the modules developed are well responded to and accepted by students and teachers. This research concludes that an e-module based on local wisdom of Lampung written batik has been developed on the material of temperature and heat.